Synovial sarcoma of the popliteal fossa - Knežević Snežana B.; Srećković Biljana R.; Vulović Jelena A.; Jandrić-Kočić Marijana S. (Archive of Oncology, 2022)
Soft tissue sarcomas are heterogeneous group of neoplasms making up to 1% of all malignant tumors in the adult population. The tumor generally appears on the extremities near large joints of middle-aged patients, especially in the popliteal fossa. Our patient presented in February 2014 due to a slowly enlarging, darker-colored swelling in the left popliteal fossa. Upon physical examination, a somewhat nodular, immobile, tender subcutaneous mass was observed. There was no locoregional lymphadenopathy. Patohistological findings showed a high-grade primary malignant mesenchymal tumor, biphasic synovial sarcoma type. The patient underwent surgery with wide surgical excision, followed by radiotherapy treatment. Magnetic resonance imagining follow up after one year revealed tumor recurrence. Neurovascular bundle involvement was detected, but without adjacent bone and muscular invasion and above-the-knee partial amputation of the left leg was performed. The intervention resulted in a remission of the neoplastic process and the patient was scheduled for regular check-ups. Broad surgical resection of the tumor with negative margins was the primary treatment in this case. Mutilating operations are necessary when anatomical structures around the tumor do not allow complete reintervention.